2014
DOI: 10.1002/2014ja020137
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ray and speed perturbations on ionospheric tomography by over‐the‐horizon radar: A new method

Abstract: Most recent methods in ionospheric tomography are based on the inversion of the total electron content measured by ground-based GPS receivers. As a consequence of the high frequency of the GPS signal and the absence of horizontal raypaths, the electron density structure is mainly reconstructed in the F2 region (300 km), where the ionosphere reaches the maximum of ionization, and is not sensitive to the lower ionospheric structure. We propose here a new tomographic method of the lower ionosphere, based on the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Tsunamis generated by earthquakes often endanger heavily populated coastal areas [e.g., Makela et al, 2011;Heki, 2011;Arrowsmith et al, 2012;Yang et al, 2012Yang et al, , 2014bAstafyeva et al, 2014;Roy et al, 2014;Jin et al, 2015]. The tsunami of 11 March 2011, following the Tohoku-Oki earthquake in Japan, caused over 20,000 fatalities.…”
Section: Introductionmentioning
confidence: 99%
“…Tsunamis generated by earthquakes often endanger heavily populated coastal areas [e.g., Makela et al, 2011;Heki, 2011;Arrowsmith et al, 2012;Yang et al, 2012Yang et al, , 2014bAstafyeva et al, 2014;Roy et al, 2014;Jin et al, 2015]. The tsunami of 11 March 2011, following the Tohoku-Oki earthquake in Japan, caused over 20,000 fatalities.…”
Section: Introductionmentioning
confidence: 99%
“…The other is obtained by scanning in frequency because the available radars are not able to scan in elevation [Coleman, 1997]. For the former type, Roy et al [2014] recently developed an ionospheric tomography method based on elevation scan data of the over-the-horizon radar Nostradamus [Bazin et al, 2006], which took into account the whole information of the radar measurement. This novel method indicated that electron density perturbations could affect the raypath geometry and consequently influence the inversion results.…”
Section: Introductionmentioning
confidence: 99%
“…To the lower ionosphere, Occhipinti setted up a new method based on the ray-tracing tool TDR to invert the propagation time 13 . For the more complex data-set of CIT, Roy et al developed a new linear regularization tomography method 14 . These methods improved the accuracy of CIT and promoted the development of CIT algorithm.…”
mentioning
confidence: 99%